Followership : what is it and why do people follow? - Lapierre, Laurent; Carsten, Melissa K. (Emerald, 2014)
This book provides a collection of new insights on the increasingly popular topic of Followership. Leadership has been written about and studied for centuries, more often than not addressing how those in leadership roles influence their followers. This represents a very leader-centric view of the leadership phenomenon, where followers are considered as passive recipients of leaders' influence. However, peoples' attempts to exercise leadership cannot be successful if there are no other people who recognize and support their leadership.